Serological Detection of Rh-Del Phenotype among Rh-Negative Blood Donors at National Blood Center, Yangon, Myanmar - Saw Thu Wah; Saung Nay Chi; Kyi Kyi Kyaing; Aye Aye Khin; Thida Aung (Advances in Hematology)
Background. Red cell Rhesus (Rh) antigen expression is influenced by the genetic polymorphism of RHD and RHCE genes and reveals serologically different reactions of RhD variants such as partial D, weak D, and Rh-Del. Serologically, Rh-Del type can only be detected by an adsorption-elution technique, and it might be mistyped as Rh-negative. The prevalence of Rh-Del has not been reported yet in Myanmar. Method. A total of 222 Rh-negative blood donors in the National Blood Center were tested for weak D and Rh-Del by indirect antihuman globulin and adsorption-elution method, respectively. RhCE typing was performed among Rh-negative and Rh-Del. Results. Of them, 75.2% (167/222) were Rh-negative, 15.8% (35/222) were Rh-Del, and 9% (20/222) were weak D. Of 202 blood donors (167 true Rh-negative and 35 Rh-Del), all of the Rh-Del positives were C-antigen-positive with 94.3% Ccee phenotype (33/35) and 5.7% CCee (2/35). Most of the Rh-negative donors (80.2%) were ccee phenotype (134/167). Conclusion. About half of Rh-Del subjects were repeated donors, and attention was needed to avoid transfusion of truly Rh-negative patients to prevent alloimmunization. It is recommended to do Rh-Del typing of Rh-negative donors who are C-antigen-positive and consider moving them to the Rh-positive pool. Further study is needed to clarify the alloimmunization status for transfusion of Rh-Del blood to Rh-negative recipients. Molecular markers for RhD-negative and D variants should be established in the Myanmar population to improve selection of antisera for Rh typing and enhance safety of the transfusion services.